2013
DOI: 10.1016/j.cplett.2013.04.063
|View full text |Cite
|
Sign up to set email alerts
|

CO2 capture and gas separation on boron carbon nanotubes

Abstract: . (2013). CO2 capture and gas separation on boron carbon nanotubes. Chemical Physics Letters, 575 ( June), 59-66. CO2 capture and gas separation on boron carbon nanotubes AbstractConcern about the increasing atmospheric CO2 concentration and its impact on the environment has led to increasing attention directed toward finding advanced materials and technologies suited for efficient CO2 capture, storage and purification of clean-burning natural gas. In this letter, we have performed comprehensive theoretical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Among the solid sorbent studies, nanotubes [15] and metal-organic frameworks [7] have been found to be excellent solid CO 2 sorbents at a low cost. Theoretically, boron-based nano-materials have also been predicted to be effective for CO 2 capture [14,[16][17][18]. Recent work by Sun et al reported that B 80 fullerene has great potential to capture CO 2 and can separate CO 2 from H 2 , N 2 , and CH 4 [17].…”
Section: Introductionmentioning
confidence: 95%
“…Among the solid sorbent studies, nanotubes [15] and metal-organic frameworks [7] have been found to be excellent solid CO 2 sorbents at a low cost. Theoretically, boron-based nano-materials have also been predicted to be effective for CO 2 capture [14,[16][17][18]. Recent work by Sun et al reported that B 80 fullerene has great potential to capture CO 2 and can separate CO 2 from H 2 , N 2 , and CH 4 [17].…”
Section: Introductionmentioning
confidence: 95%
“…An all electron double numerical atomic orbital basis set augmented by d-polarization functions (DNP) was used. This level of theory has been used to successfully determine the geometrical, energetic and electronic structural properties of interactions of many small molecules and nano-subtracts [31][32][33][34]. All the ccalculations have been performed using DMol3 module in Materials Studio [35][36].…”
Section: Quantum Chemical Calculationmentioning
confidence: 99%
“…This calculational level has been used to successfully study adsorptions, desorption and the reaction mechanisms of some gases on boron-containing nanomaterials. 5,[25][26][27][28] The adsorption energies (E ads ) of N 2 and CH 4 on B 36 N 36 are calculated from Eq. (1): E ads = (E B36N36 + E gas ) -E B36N36-gas…”
Section: Methodsmentioning
confidence: 99%